(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
The methodology of teaching the learners to participate successfully in all areas of communication in foreign languages is the central concept of the pedagogical researches of recent years. This article demonstrates that philosophy of teaching is essential in second language acquisition, some important aspects of teaching and my own teaching philosophy and its effectiveness.